Not all durations of preheart transplant mechanical ventilation portend inferior post‐transplant survival in children. (7th November 2022) - Greenberg, Jason W.; Kulshrestha, Kevin; Dani, Alia; Winlaw, David S.; Lehenbauer, David G.; Chin, Clifford; Lorts, Angela; Gist, Katja M.; Zafar, Farhan; Morales, David L. S.
Abstract: Background: Mechanical ventilation prior to pediatric heart transplantation predicts inferior post‐transplant survival, but the impact of ventilation duration on survival is unclear. Methods: Data from the United Network for Organ Sharing and Pediatric Health Information System were used to identify pediatric (<18 years) heart transplant recipients from 2003 to 2020. Patients ventilated pretransplant were first compared to no ventilation, then ventilation durations were compared across quartiles of ventilation (≤1 week, 8 days–5 weeks, >5 weeks). Results: At transplant, 11% (511/4506) of patients required ventilation. Ventilated patients were younger, had more congenital heart disease, more urgent listing‐status, and greater rates of nephropathy, TPN‐dependence, and inotrope and ECMO requirements ( p < .001 for all). Post‐transplant, previously ventilated patients experienced longer ventilation durations, ICU and hospital stays, and inferior survival (all p < .001). Hospital outcomes and survival worsened with longer pretransplant ventilation. One‐year and overall survival were similar between the no‐ventilation and ≤1 week groups ( p = .703 & p = .433, respectively) but were significantly worse for ventilation durations >1 week ( p < .001). On multivariable analysis, ventilation ≤1 week did not predict mortality (HR 0.98 [95% CI 0.85–1.43]), whereas ventilation >1 week did (HR: 1.18 [1.01–1.39]). Conclusions: Longer pretransplant ventilation portends worse outcomes, although only ventilation >1 week predicts mortality. These findings can inform pretransplant prognostication.